A comprehensive evaluation for different post-curing methods used in stereolithography additive manufacturing. (August 2020) - Zhao, Jing; Yang, Yiran; Li, Lin
Highlights: Ultraviolet, conventional oven and microwave post-curing processes are evaluated. Mechanical property, surface quality, dimensions and sustainability are considered. Ultraviolet post-curing can enhance the ultimate tensile strength by 70.83 %. Post-curing generally can lead to volume shrinkage and worse surface quality. Abstract: Additive manufacturing, as one of the most promising advanced manufacturing technologies, has been obtaining increasing public interest since its first emergence in the 1980s. Owing to its unique layer-wise production method, additive manufacturing can fabricate complex parts and reduce the production time. Limited by current processes and materials, the overall performance of additive manufactured products is not always exceptional especially in terms of print quality, mechanical property, and sustainability. To address this issue, post-curing is often used to further alter the part performance. In this paper, a comprehensive evaluation is conducted for three most popular post-curing processes, i.e., conventional oven, microwave oven, and Ultraviolet chamber, considering their capabilities of altering ultimate tensile strength, hardness, dimensional variations, surface roughness, production cost, and energy consumption. To characterize the relation between post-curing process parameters and resulting performance, both analytical and statistical models are established and evaluated. The case study results suggest that various post-curing processes can cause different influences on the part performance. As an example, ultimate tensile strength can be improved by 70.83 % and 15.01 % when Ultraviolet and microwave oven are used, respectively. In addition, optimal post-curing strategies under different constraints are obtained based on established models, which will provide useful insights for post-curing process planning and optimization.